First report of Lasiodiplodia brasiliense causing maize stalk rot. - AGUIAR, F. M. (2018)
Maize stalk rot can lead to major corn yield losses in Brazil and worldwide. Maize stalks exhibiting tiny black specks or light brown lesions were collected in the city of Luís Eduardo Magalhães. Based on morphological characteristics and molecular assays, the fungus was identified as Lasiodiplodia brasiliense. This is the first report of maize stalk rot caused by L. brasiliense.